PERAN PENDIDIKAN INKLUSIF DALAM PEMBERDAYAAN ANAK BERKEBUTUHAN KHUSUS DI KOTA MAKASSAR - haerul; Nasir (Universitas Islam Raden Rahmat Malang, 2025)
Inclusive education is an approach that aims to ensure access and equity in education for all children, including children with special needs (ABK). However, its implementation at the school level still faces various challenges. This study aims to analyze the role of inclusive education in the empowerment of ABK in Makassar City. Using a descriptive qualitative approach, data were obtained through observation, interviews, and documentation in several inclusion schools. The results of the study show that inclusive education encourages independence, social participation, and to a limited extent supports the academic potential of ABK. Supporting factors include school commitment, parental support, and cross-sector cooperation. The main obstacles are the limited number of accompanying teachers, lack of training, and social stigma. The conclusion of this study emphasizes that inclusive education has the potential as a tool for empowering ABK, but it still requires systemic strengthening and school culture transformation.